Prosecutors in the boardroom : using criminal law to regulate corporate conduct - Barkow, Anthony S.; Barkow, Rachel E. (NYU series in social and cultural analysis., 2011)
Who should police corporate misconduct and how should it be policed? In recent years, the Department of Justice has resolved investigations of dozens of Fortune 500 companies via deferred prosecution agreements and non-prosecution agreements, where, instead of facing criminal charges, these companies become regulated by outside agencies. Increasingly, the threat of prosecution and such prosecution agreements is being used to regulate corporate behavior. This practice has been sharply criticized on numerous fronts: agreements are too lenient, there is too little oversight of these agreements, a.